Agama, Covid-19, dan Tatanan Budaya Baru: Pengabdian Kalangan Muda NU Soloraya terhadap Pandemi Covid-19 - Mibtadin, Mibtadin; Masamah, Ulfa; Fatimah, Lilis (Transformatif : Jurnal Pengabdian Masyarakat, 2022)
Covid-19 appeared in early 2020 until now its spread has not been cut off and has changed the order of life, including religion. This article describes the role of NU Soloraya's youth in responding to the spread of Covid-19. This research is descriptive qualitative in nature and uses a sociological approach to religion. Data collection was carried out through observation, in-depth interviews, and documentation. Data were analyzed using an interactive analysis model. States to limit its spread by implementing health protocols. The youth of NU Soloraya responded by providing spiritual guidance and also encouraging the congregation to actively develop moderation theology, namely the theology of caring for others that is manifested in the spirituality of humanity. They position themselves as facilitators, animators, enablers, catalysts so that they can become opinion leaders and balance discourse about Covid-19. With empathy, sympathy, and concern, they strengthen social resilience so that the majlis taklim network and Islamic boarding schools become social capital to tackle Covid-19.